2006
DOI: 10.1002/mrdd.20097
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of maltreatment of people with intellectual disabilities: A review of recently published research

Abstract: Maltreatment can have a profound adverse effect on the health of individuals with intellectual disabilities (ID). People with ID may also be more likely to experience maltreatment than other groups. Historically, data on prevalence of maltreatment among people with ID have been sparse and methodologically weak but have suggested that the scope of the problem is considerable. Studies published between 1995 and 2005 were reviewed to determine estimated maltreatment prevalence among people with ID based on recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
107
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(126 citation statements)
references
References 40 publications
7
107
1
8
Order By: Relevance
“…Balogh et al, 2001;Sobsey, 2002). This increased risk is part of a broader pattern of victimization and maltreatment of children and adults with disabilities, including physical disabilities and learning disabilities (Hassouneh-Phillips & Curry, 2002;Horner-Johnson & Drum, 2006;Li, Ford, & Moore, 2000;Little, 2004;Martin et al, 2006;McCarthy, 1998;Sullivan & Knutson, 2000).…”
mentioning
confidence: 95%
“…Balogh et al, 2001;Sobsey, 2002). This increased risk is part of a broader pattern of victimization and maltreatment of children and adults with disabilities, including physical disabilities and learning disabilities (Hassouneh-Phillips & Curry, 2002;Horner-Johnson & Drum, 2006;Li, Ford, & Moore, 2000;Little, 2004;Martin et al, 2006;McCarthy, 1998;Sullivan & Knutson, 2000).…”
mentioning
confidence: 95%
“…Prevalence rates of abuse of people with disabilities vary from three to seven times more than reported for people without disabilities (Horner- Johnson & Crum, 2006), although this is almost certainly underreported Powers et al, 2002). Many contextual or ecological factors place them at a heightened risk for abuse as well as inhibit reporting and stopping abuse, including (a) reliance on abusive caregivers for care and support (Chang et al, 2003;Oschwald et al, 2009), (b) lack of accessible alternative options to leave an abusive situation (Chang et al, 2003;Powers et al, 2002), (c) limited social opportunities to building Downloaded by [University of North Texas] at 03:03 02 December 2014 social intuition (Curry, Hassouneh-Phillips, & Johnston-Sliverberg, 2001), and (d) tendency of support professionals to discredit reports of abuse (Curry et al, 2001;Powers et al, 2002).…”
Section: Abuse and Neglectmentioning
confidence: 92%
“…Instances of abuse and neglect occur at a much higher rate and for longer durations for this population than for people without disabilities and often includes malicious acts directly tied to the person's disability (Chang et al, 2003;Horner-Johnson & Crum, 2006;Powers et al, 2002). The types of abuse targeting them include physical, sexual, emotional, and verbal abuse, as well as withholding supports, financial exploitation, manipulation of medications, and harming equipment (Powers et al, 2002).…”
Section: Abuse and Neglectmentioning
confidence: 96%
“…Data derived from these studies report prevalence rates of up to ten times higher than people without an ID, especially in sexual offenses (Brown, Stein, & Turk, 1995;Harrel, Truman, Curto, Thomas, Quinn, & James, 2012;McCarthy & Thompson, 1997;Sobsey, 1994;Verdugo, Alcedo, Bermejo, & Aguado, 1999. Horner-Johnson and Drum (2006) reviewed the literature on the prevalence of abuse of people with an ID between 1995 and 2005. They found that (although studies were few and the methodologically was poor) studies confirmed that this was the most vulnerable population.…”
Section: Introductionmentioning
confidence: 99%